2001
DOI: 10.1089/10962960152813313
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Shock Resuscitation with a Low Molecular Weight Starch Reduces Neutrophil-Endothelial Interactions and Vessel Leakage in vivo

Abstract: 10% pentastarch reduces RL-associated EC-PMN interactions and vessel leakage following hemorrhagic shock. These results support the use of low MW starches to resuscitate hemorrhagic shock, potentially reducing PMN-mediated tissue injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 73 publications
(72 reference statements)
1
12
0
Order By: Relevance
“…This is consistent with other reports on improved microvascular permeability (7,9,17) and other indirect parameters of a microcirculatory improvement, such as the restored tissue oxygenation (2, 7) after HES treatment. Information is also available concerning the better efficacy of HES in comparison with GEL or DEX in influencing these parameters (24,25).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with other reports on improved microvascular permeability (7,9,17) and other indirect parameters of a microcirculatory improvement, such as the restored tissue oxygenation (2, 7) after HES treatment. Information is also available concerning the better efficacy of HES in comparison with GEL or DEX in influencing these parameters (24,25).…”
Section: Discussionsupporting
confidence: 93%
“…It has also been suggested that colloid solutions affect PMN adherence directly, by influencing the adhesion molecule expression independently of microhemodynamic changes (17). However, microhemodynamics and leukocyte adhesion are interrelated phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have also shown similar results in an in vivo, intravital microscopic model of hemorrhagic shock in which PMN rolling events in transilluminated cremaster muscle were shown to decrease in association with HES administration. (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite this evidence of increased PMN activity, other studies have demonstrated that HES infusion after hemorrhage does not adversely affect cell-mediated immune functions, and may produce salutary effects on macrophage functions (18,19). Additionally, low-molecularweight colloids have been shown to reduce PMN-endothelial interactions and vessel leakage after hemorrhagic shock (20). It remains unclear how these conflicting findings relate to the functional state of the PMN.…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate cellular activation and their vigorous interaction with the endothelial lining are responsible for local and systemic release of toxic mediators, in particular reactive oxygen species (ROS) that cause vessel injury and leakage. When different methods to determine permeability changes and estimate fluid sequestration and organ edema were used, the application of hypertonic saline in various models of organ damage revealed less extravasation and leakage than did normotonic crystalloids [44][45][46][47]. Newer crystalloids, such as ethyl pyruvate solution, might even be superior to hypertonic saline because of their unique ROS scavenging action [48] and anti-inflammatory property [49].…”
Section: Cellular Effects Of Hypertonic Crystalloidsmentioning
confidence: 99%